Beyond the Biophysical Knowledge, Culture, and Politics in Agriculture and Natural Resource Management - German, Laura A.; Ramisch, Joshua J.; Verma, Ritu.; SpringerLink (Online service) (Dordrecht : Springer Netherlands : Imprint: Springer, 2010)
Beyond the Biophysical argues for an interdisciplinary perspective on agriculture, natural resource management (NRM), and international development practice that extends beyond a purely biophysical orientation. Biophysical interventions succeed or fail not simply on their own merits but within a context shaped by knowledge, culture, and power. The original case studies and conceptual syntheses (from Africa, Asia, and Latin America) analyze some of the challenges and (3z(Bmisadventures(3y (Bassociated with past and current development approaches and practice. They apply contemporary, critical social science to make sense of these realities and offer concrete recommendations for moving beyond them. With them, we hope to make social science theory, the challenges faced by socio-cultural scientists working in arenas dominated by other disciplines, and the potentially unique contributions of social science to agriculture and natural resource management more accessible to biophysical scientists, development practitioners, and those exploring the socio-cultural sciences as a possible career path. The book is broken into four main sections: (1) an introduction to concepts and the volume; (2) a series of chapters designed to foster a rethinking of common concepts and assumptions in agricultural development and natural resource management; (3) a set of case studies and conceptual overviews on the interface of knowledge, culture, and politics; and (4) a set of chapters on institutional disconnects and innovations to expand institutionalized thinking and practice.s
Beyond Biophysical Assumptions -- Agriculture, Natural Resource Management, and (3z(BDevelopment(3y (BBeyond the Biophysical -- Beyond the Invisible: Finding the Social Relevance of Soil Nutrient Balances in Southern Mali -- The (3z(BDemonization(3y (Bof Rainforest Migrants, or: What Conservation Means to Poor Colonist Farmers -- Beyond Biodiversity: Culture in Agricultural Biodiversity Conservation in the Himalayan Foothills -- Local Knowledge and Scientific Perceptions: Questions of Validity in Environmental Knowledge -- Power Dynamics at the (3z(BDevelopment Interface(3y (B-- (3z(BOpting Out(3y(B: A Case Study of Smallholder Rejection of Research in Western Kenya -- Natural Resource Management in an Urban Context: Rethinking the Concepts of (3z(BCommunity(3y (Band (3z(BParticipation(3y (Bwith Street Traders in Durban, South Africa -- The Deliberative Scientist: Integrating Science and Politics in Forest Resource Governance in Nepal -- Common Property Regimes: Taking a Closer Look at Resource Access, Authorization, and Legitimacy -- Institutional Disjunctures and Innovations -- Innovative Farmers, Non-adapting Institutions: A Case Study of the Organization of Agroforestry Research in Malawi -- Framing Participation in Agricultural and Natural Resource Management Research -- Anthro-Apology? Negotiating Space for Interdisciplinary Collaboration and In-Depth Anthropology in the CGIAR -- Who Is Fooling Whom? Participation, Power, and Interest in Rural Development.s
Keywords: Environmental sciences; Agriculture; Forests and forestry; Sustainable development; Anthropology; Human Geography; Environment; Sustainable Development; Anthropology; Sociology, general; Human Geography; Agriculture; Forestry